Oral health indices and microbiota populations of adult cats consuming wet or dry diets - Oba, Patrícia M.; Swanson, Olivia R.; Pavlovsky, Gene; Dupleix, Chloe R.; Sharping, Stephanie C. J.; Swanson, Kelly S. (Frontiers in Veterinary Science, 2025)
Oral microbiota play a critical role in feline periodontal disease, with wet diets being associated with poor oral health. Because the oral microbial communities of cats remain underexplored, this study aimed to evaluate differences in the oral health indices and microbiota of cats fed a dry or wet diet. Twenty healthy adult cats had their teeth cleaned and polished. Cats were randomly allotted to a dry or wet diet and fed for 28 weeks. At that time, sulfur-containing compound concentrations and salivary pH were measured, plaque, calculus and gingivitis scores were assessed by a blinded veterinarian, and supragingival and subgingival plaque samples were collected for microbiota analysis. Microbiota data were evaluated using QIIME2. All other data were analyzed using the Mixed Models procedure of SAS. Cats fed the dry diet had lower tooth calculus coverage and thickness than cats fed the wet diet. Gingivitis scores were higher in cats fed the wet diet than those fed the dry diet. Other clinical measures did not differ. Bacterial alpha diversity measures on supragingival plaque were lower in cats fed the wet diet than those fed the dry diet. Bacterial beta diversity measures revealed distinct microbial communities between diet groups, with numerous changes to bacterial phyla and genera relative abundances. Compared with cats fed the dry diet, cats fed the wet diet had higher relative abundances of Bacteroidota and Bacteroides in supragingival samples and greater relative abundances of Synergistota, Bacteroides, Fretibacterium, Campylobacter, and Christensenellaceae R-7 group in subgingival samples. In contrast, cats fed the dry diet had higher relative abundances of Proteobacteria, Streptococcus, Luteimonas, Lautropia in supragingival plaque than those cats fed the wet diet. Although most clinical indices did not differ between groups, the reduced calculus scores, enrichment of health-associated bacteria and reduction in disease-associated bacteria suggest oral health benefits of dry diets.